Fast Sodium Storage with Ultralong Cycle Life for Nitrogen Doped Hollow Carbon Nanofibers Anode at Elevated Temperature. Issue 9 (11th March 2020) - Chen, Zhuowen; Duan, Huanhuan; Xu, Zhiguang; Chen, Caihong; Yan, Yurong; Wu, Songping
Abstract: Sodium ion batteries have been suffering low reversible capacity, poor rate, and less cycling reliability upon sodiation/desodiation. To address those formidable issues, electrospinning combined with hard template route is adopted here to collect loofah‐like nitrogen‐doped hollow carbon nanofibers (NHCNFs) derived from sustainable and low‐cost resources, that is, renewable acrylic yarn. NHCNFs render a remarkable reversible capacity of 143 mAh g −1 for 5000 cycles at a current density of 10 A g −1 at ambient temperature. More importantly, NHCNFs possesses an impressive capability in tackling the elevated temperature environment, affording an admirable reversible capacity of 156 mAh g −1 at a high rate of 15 A g −1 even after 10 000 cycles under 50 °C. These superior performances could be attributed to the combination of the following factors: delicately designed microstructure with hollow bead‐like channels, pseudocapacitive behavior and accelerated kinetics. Such an excellent attribute enables loofah‐like NHCNFs to be a promising low‐cost and environment‐friendly anode for sodium ion rechargeable batteries. Abstract : Electrospinning is adopted to collect loofah‐like N‐doped CNFs by combining with hard template, rendering an admirable reversible capacity when utilized as anode of SIBs.